Evaluation of Taurine by HPTLC Reveals the Mask of Adulterated Edible Bird's Nest. (12th August 2013) - Teo, Peishan; Ma, Fucui; Liu, Daicheng
Abstract : Detection of amino acid is an effective and common method to determine adulteration in edible bird's nest. Therefore, a simple and sensitive method was developed to detect taurine for determining adulteration in edible bird's nest in the future. Sample was separated on precoated silica gel GF254 high-performance thin layer chromatographic plates. Separation of taurine was performed by n-propyl alcohol : ethanol : water : glacial acetic acid (5.2 : 0.8 : 2 : 2, v : v : v : v). Densitometric analysis of taurine was carried out in the absorbance mode at 485 nm. The method was validated for precision, intra- and interday variation, and recovery. This study proved that high-performance thin layer chromatography is a simple, rapid, precise, and selective method for qualitative and quantitative analysis of taurine in edible bird's nest.